Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus dan Dana Bagi Hasil Terhadap Belanja Daerah Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2016-2020 - Maryati, Sri; Muttaqin, Ibnu (Majors Accounting, Faculty of Economics and Business, Universitas Pancasakti Tegal, 2021)
The purpose of this study was to determine the effect of Regional Original Income, General Allocation Funds, Special Allocation Funds and Revenue Sharing Funds on Regency/City Regional Expenditures in Central Java Province in 2016-2020. The research method used is quantitative, using secondary data types, then data is collected and processed using the SPSS 22 application. The population and samples used in this study are Regency/City budget realization reports for a 5-year period (2016-2020). This study uses descriptive statistical data analysis, while the unit of analysis used is multiple linear regression analysis. Based on the results of the study, it was found that Regional Original Income, General Allocation Funds, Special Allocation Funds and Revenue Sharing Funds had a positive effect on Regional Expenditures in Central Java Province in 2016-2020.